Optimization of biochar and drip irrigation to improve chili yield and soil properties - WIDOWATI WIDOWATI; SIRILUS MARIO BIRU; I MADE INDRA AGASTYA; UTIK TRI WULAN CAHYA; RETNO WILUJENG (Smujo International, 2025)
Abstract. Widowati, Biru SM, Agastya IMI, Cahya UTW, Wilujeng R. 2025. Optimization of biochar and drip irrigation to improve chili yield and soil properties. Asian J Agric 9: 442-453. Cayenne pepper (Capsicum frutescens) is an important horticultural crop in Indonesia; however, its yield remains below optimal despite rising demand. This study intends to (i) assess changes in soil bulk density, particle density, and porosity; (ii) evaluate the effects of irrigation techniques and the application of biochar on chili yields; and (iii) identify the best combination for optimizing resource usage and yield. Eight different treatment combinations, each repeated four times, were used in a nested randomized design study conducted in Tunggulwulung Village, Malang. As the primary factor, the treatments included two main irrigation techniques (conventional and drip), which were further subdivided with different rates of biochar application (0%, 2%, 4%, and 6%). There were 160 pots total, with five plants per treatment acting as experimental units. Rice husks that had been pyrolyzed for three to four hours at 600°C were the source of the biochar. According to the results, adding biochar to conventional irrigation increases fruit weight by 125% and yield by about 130%. Drip irrigation with 4% biochar, on the other hand, is the most successful technique and yields much larger improvements, increasing fruit weight by 764% and fruit yield by 324%. Drip irrigation is more effective and yields better results than conventional irrigation, especially when combined with rice husk biochar. Furthermore, soil porosity and water use efficiency are significantly increased when 4% and 6% doses of biochar are added to drip irrigation systems.